A pragmatic framework to score and inform about the environmental sustainability and nutritional profile of canteen meals, a case study on a university canteen. (20th June 2018) - Schaubroeck, Thomas; Ceuppens, Siele; Luong, Anh Duc; Benetto, Enrico; De Meester, Steven; Lachat, Carl; Uyttendaele, Mieke
Abstract: This paper presents a pragmatic framework to inform stakeholders about the sustainability of canteen meals. The framework consists of four parts: (1) an ecological scoring system, based on life cycle assessment results, to score the ecological impact of meals or their components, from which the customer can select to compose a meal; (2) a nutritional scoring of meals based on meeting nutritional criteria; (3) a scoring system to assess the efforts undertaken by the canteen suppliers with regard to sustainable production and management and (4) collected information on relevant topics in food sustainability not covered in previous parts. The framework has furthermore been customized for and applied to the canteen of Ghent University. In light of part 1, several methods to characterize the environmental impact of food products were benchmarked, pinpointing the ecological footprint, the amount of land needed for production and to sequester CO2, as most appropriate one. Moreover, the ecological footprint of harvested fish was newly characterized as amount of land indirectly needed for their growth in nature. This highlighted the much lower (2–15 times) ecological footprint of aquaculture than caught fish products, according to this method. The ecological scoring system was consequently based on the ecological footprint but also the carbon footprint due to its relevance, covering the discrepancy between meat, with relatively higher carbon footprint, and caught fish products, with relatively higher ecological footprint. Besides a promotion of more sustainable meals, following guidelines and conclusions were derived: (1) the ecological impact depends on more than just the main component, e.g. frying oil contributes the most to the ecological footprint of fries, and type of food, e.g. a portion 'pangasius orientale' (fish), has an about 30% lower ecological footprint than a portion 'ratatouille vegetables' (vegetarian); (2) lower salt content, which can mount up to >80% for a meal, to improve nutritional value and (3) provide a variety of portion sizes because nutritional demand varies. Although further improvement is needed, the framework is prominent because of the better characterization of environmental impact, its pragmatic coverage of various sustainability aspects through its four parts, feedback to all stakeholders and its easiness of application for a manifold of meals. Graphical abstract: Image 1 Highlights: Ecological footprint was assessed for caught fish and 2–15 times that of cultivated. A framework of indicators is provided to inform canteen stakeholders. Ecological score per meal component, from 1 to 8, is based on the EF. Caught fish scored higher for the ecological, while meat for the carbon footprint. Nutritional score per meal, from 1 to 8, is based on meeting nutritional criteria.